TALKING STICK : A LEARNING MODEL TO IMPROVE STUDENT'S MATHEMATICS LEARNING INTEREST AND ACHIEVEMENT IN ELEMENTARY SCHOOLS - Rika Wulandari (Widyagogik, 2021)
The purpose of this study was to determine how the steps of the talking stick type of cooperative learning model assisted with question cards that can improve student learning outcomes and interest. The research was conducted using this type of classroom action research. The stages of classroom action research carried out include: plan, act, observe, reflect. The research was conducted at SDN Kara I, Sampang to 9 Grade III students. The results of the study indicate that the steps of the talking stick type of cooperative learning model assisted with question cards that can improve learning outcomes and student interest are: the teacher organizes students into several groups, each group consisting of four students heterogeneously. The teacher explains the rules of the game, namely the game is done by running a stick while singing, if the teacher says "stop" then the last one holding the stick gets a question by taking a question card containing the question, but if the student cannot answer it can be helped by a group of friends. Likewise so on ". After finishing the teacher asks students to conclude the material that has been studied then divides the evaluation questions. The percentage of classical completeness of learning outcomes reached 77.77% with an average learning outcome also increased from 66.1 to 77.77. Likewise with students' interest in learning, on average the results of filling out the interest questionnaire were in the category of very fond of the cooperative learning model type talking stick assisted question card that was done.